Karakterisasi dan Identifikasi Rhizobakteri Asal Mangrove Tanjung Pilawang sebagai Biokontrol dan Agen Hayati Pertumbuhan Tanaman - Maatoke, Cornelia Dolfina; Gisisi, Deiby Elsa; Girsang, Yusi Firdawati (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Rhizobacteria are a type of microbe that has an important role in providing nutrients to plants. Rhizobacteria live in symbiosis with plant roots, where their activity has a significant influence on plant growth and development. Various microbes that have the potential to stimulate plant growth are thought to reside in mangrove root areas. The aim of this research is to determine the type of rhizobacteria of the Tanjung Pilawang mangrove, Gura Village, Tobelo District, North Halmahera Regency which is capable of inhibiting the growth of the fungus Collectotricum capsici and dissolving phosphate to be used as a biocontrol and biological agent for plant growth. The research methods used include the isolation stage, selection and characterization stages, and identification stages. The results of the research showed that 11 isolates of rhizobacteria were isolated from Tanjung Pilawang mangrove soil, of these 11 isolates there were two isolates that had the potential to inhibit the growth of the pathogenic fungus Colletotricum capsici and were able to dissolve phosphate, where each isolate was able to provide a Dissolution Index (IP) value. the highest is 2.85 mm and 1.91 mm. After identification, the two isolates were identified as Bacillus subtilis (RTM 10) and Pseudomonas sp (RTM 06), so that these two bacteria have potential as biocontrol and biological agents for plant growth.